PENGELOLAAN LIMBAH KAWASAN INDUSTRI KECIL DI KOTA TEGAL - Setiyono, Setiyono; Wahjono, Heru Dwi (Center for Environmental Technology, 2006)
Tegal is a maritime town that mostly its resident has living as fisherman. Most existing industry in this town is fishery industry. Besides fishery industry, other small industrial also produce waste water which together with domestic waste water partake to contaminate Gung river, Sibelis river, Kemiri river and other channel which pass through Tegal town. Tegal town government trough the Office Operation of Environmental Impact (KEPADEL) have conducted various effort to reduce the impact of environmental contamination by giving counseling, training and other compilation of book containing information technology and technical guidance of waste water management to industrial activity exist in Tegal. With construction which continues to be conducted by KAPEDAL, we expected that the environmental quality in this town will change with progressively goodness.Ã‚Â Kata Kunci : Kawasan Industri, Limbah Cair Industri, Pencemaran Lingkungan, InformasiTeknologi Pengelolaan Limbah.